2019
DOI: 10.1038/s41598-019-38823-0
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of treatment proficiency of hydroxyurea treated β-thalassemia serum samples through nuclear magnetic resonance based metabonomics

Abstract: β-Thalassemia is a widespread autosomal recessive blood disorder found in most parts of the world. Fetal hemoglobin (HbF), a form of hemoglobin is found in infants, replaced by adult hemoglobin (HbA) after birth. Hydroxyurea (HU) is one of the most effective HbF inducer used for the treatment of anemic diseases. We aimed to improve the understanding of HU therapy in β-thalassemia by metabonomics approach using 1H NMR spectroscopy. This study includes 40 cases of β-thalassemia before and after HU therapy along … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Moreover, HYD and DFMO have been documented to be useful in chemotherapy for anemia, and sleeping sickness in humans [16,22] and the present study showed their efficacy against mice infected with B. microti, and thus, they might be used as an alternative chemotherapy for humans infected with B. microti after some clinical studies. However, PCR assay should be used alongside optical microscopy in future similar works to detect parasites DNA from in vitro cultures as well as from peripheral blood of animal models in vivo to ensure a total clearance of parasites.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Moreover, HYD and DFMO have been documented to be useful in chemotherapy for anemia, and sleeping sickness in humans [16,22] and the present study showed their efficacy against mice infected with B. microti, and thus, they might be used as an alternative chemotherapy for humans infected with B. microti after some clinical studies. However, PCR assay should be used alongside optical microscopy in future similar works to detect parasites DNA from in vitro cultures as well as from peripheral blood of animal models in vivo to ensure a total clearance of parasites.…”
Section: Discussionsupporting
confidence: 57%
“…Cokic et al [15] documented that HYD is well absorbed in vivo, converted to free radical nitroxide and transferred to the cells, whereas the tyrosyl free radical suppression happens at ribonucleotide reductase active site, thereby inhibiting the enzyme. Moreover, HYD has been documented as the best choice for anemic disease treatment such as β-thalassemia [16]. HYD reportedly possesses an antiparasitic activity through blocking Toxoplasma gondii tachyzoite replication [17] and synchronizing the kinetoplast DNA of several parasites, such as Crithidia fasciculate, Leishmania major, L. infantum, L. tarentolae, Trypanosoma brucei, and T. cruzi [16,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although normalization details were not specified in all the studies, the normalization strategy was mainly dependent on the sample type. Overall, serum and plasma NMR data were preferentially normalized to total area [ 40 , 41 , 46 , 47 , 49 , 51 , 52 , 60 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 ], although probabilistic quotient normalization [ 26 , 48 , 77 ] and other normalization procedures, such as glucose [ 78 ] or internal standard normalization [ 39 ], were applied in some studies. For urine normalization, total area [ 42 , 67 ] and creatinine signal were the methods most frequently used [ 44 , 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Before the onset of clinically detectable symptoms, alterations in serum metabolites offers a potential diagnostic biomarker for disease status and predicting response to treatment [15][16][17]. While previous studies identified lipid metabolism as being impacted by the disease and its treatment, the coverage of lipids was limited, mostly to fatty acids.…”
Section: Introductionmentioning
confidence: 99%